2015
DOI: 10.1093/neuonc/nov045
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of 151 pediatric low-grade gliomas reveal molecular differences associated with location and histological subtype

Abstract: Expression profiling of PLGGs reveals significant differences associated with tumor location, histology, and BRAF genomic status. Supratentorial PAs, in particular, are enriched in inflammatory pathways that appear to be tumor-related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…BRAF mutations have been sparsely seen among adult lowgrade glial-neuronal tumors (49)(50)(51) LGG, a group comprised primarily of gangliogliomas, diffuse astrocytoma, DNET, and a small proportion of pilocytic astrocytomas, also demonstrating that this cluster was significantly enriched for a significant number of gene sets that together suggested a neuronal signature (55). Furthermore, they did not detect any alteration in gene expression profile among BRAF-altered tumors when compared with wild-type BRAF in LGG.…”
Section: Braf Mutations Are Common In Dig/diamentioning
confidence: 99%
“…BRAF mutations have been sparsely seen among adult lowgrade glial-neuronal tumors (49)(50)(51) LGG, a group comprised primarily of gangliogliomas, diffuse astrocytoma, DNET, and a small proportion of pilocytic astrocytomas, also demonstrating that this cluster was significantly enriched for a significant number of gene sets that together suggested a neuronal signature (55). Furthermore, they did not detect any alteration in gene expression profile among BRAF-altered tumors when compared with wild-type BRAF in LGG.…”
Section: Braf Mutations Are Common In Dig/diamentioning
confidence: 99%
“…While the presence of ganglion cells in DIG could suggest some biological overlap with conventional ganglioglioma, the latter lacks the very young patient age, massive size, and rich desmoplastic investiture of DIG. Gangliogliomas in pediatric patients are known to harbor v‐Raf murine sarcoma viral oncogene homolog B ( BRAF ) V600E mutations, variably reported as 35%, 50%, and >60% of cases. This has prompted several previous studies looking for BRAF mutations in DIAs and DIGs.…”
Section: Introductionmentioning
confidence: 99%
“…These have shown that histologically identical tumours have different methylation and gene expression profiles depending on their location and that these differences are associated with genes involved in nervous system development pathways (Bergthold et al, 2015;Lambert et al, 2013;Sharma et al, 2007;Tchoghandjian et al, 2009). Here, we have provided further evidence in support of this concept, identifying location-specific differential methylation of genes involved in embryonic nervous system development, several of which have been previously reported, including LHX2, NR2E1, SIX3, PAX3 and IRX2 (Bergthold et al, 2015;Lambert et al, 2013;Sharma et al, 2007;Tchoghandjian et al, 2009). Additionally, our analysis showed that many of the location-specific differences identified in DNA methylation profile were reflected in control adult brain, which supports the concept that tissue of origin is an important driver of DNA methylation profile of histologically similar tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is no difference in the frequency of copy number variations according to PA location, there is evidence to show that tumour location is associated with specific MAPK pathway alterations (Jones et al, 2006;Pfister et al, 2008). For example, KIAA1549-BRAF fusions are more common in posterior fossa tumours (up to 90%), compared to supratentorial tumours (33-59%), and BRAF V600E mutations are more frequent in supratentorial tumours (~18%) than those in the posterior fossa (~3%) (Bergthold et al, 2015;Horbinski, 2013;Zhang et al, 2013). These location-specific alterations are also seen in gene expression analyses that show significant differences between supratentorial and infratentorial PAs and between hypothalamic/chiasmatic and posterior fossa PAs (Bergthold et al, 2015;Sharma et al, 2007;Tchoghandjian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%